Windows and Doors in Wuthering Heights - Bemáth Klára; Csetényi Korinna (2007)
This thesis examines the main symbolical meanings of doors and windows in Emily Bronta's Wuthering Heights. A closer look is taken at the psychological background of the main characters and their relationships in the situations where the window and door motifs appear. It is taken into consideration how the motifs of doors and windows help to show and understand the hidden intentions and psychological problems of the main characters. The narrators' points of view are also examined, together with their effects on the plot and their connections with the other characters of the novel.
Keywords: Pedagógusképzés